Effect of lactic acid and galactose on the storage stability of lactose rich permeate powders - Thorakkattu, Priyamvada (Kansas State University, 2020)
Deproteinized whey (DPW) and milk permeate (MP) are coproducts obtained during the ultrafiltration of whey and milk, respectively. Then, they undergo unit operations like evaporation, crystallization, and spray drying resulting in a non-hygroscopic, free-flowing powder. Typically, DPW powders contain 76-85% lactose, 2-7% protein, 3-4.5% moisture, and 8-11% ash. On the other hand, MP powders typically contain 78-88% lactose, 3-5% protein, 3-4.5% moisture, and 8-11% ash. These high lactose dairy ingredients are widely used in baked goods, soups, sauces, confectionery, drink mixes, snack foods, beverages, and in certain ice cream formulations. Lactose is present in all dry dairy ingredients, with levels ranging from <2% (caseinates, milk protein isolates) to 100% in lactose powders. Lactose rich powders may undergo chemical and physical changes such as Maillard browning and caking during storage. The presence of lactose in coproducts can adversely affect the powder properties and can lead to stickiness and caking. Furthermore, being a reducing carbohydrate, lactose can also participate in the Maillard reaction causing discoloration of powders during storage. Moreover, the presence of impurities like proteins, peptides, free amino acids, minerals, glucose, and galactose can also significantly influence the shelf-life of lactose rich coproducts. Understanding the effects of various intrinsic and extrinsic factors will improve the stability of lactose-rich-coproducts. This study aimed to investigate the effect of different levels of lactic acid and galactose on the physical, chemical, and thermal properties of DPW and MP powders. For the DPW powder study, two lots of concentrated permeate with total solids of ~77% were procured from a commercial manufacturer and were adjusted to 45% total solids with water and samples were divided into 9 subsamples with varying levels of lactic acid and galactose. For the MP powder study, two lots of MP powders were procured from a commercial manufacturer and were reconstituted to 45% total solids and this was divided into 4 subsamples with varying levels of lactic acid and galactose. The samples were then dried in a lab-scale spray dryer with inlet and outlet temperatures of 180 and 85°C, respectively. The spray dried DPW powders were sealed and stored at 25°C for 0 (control), 30, 60, 90, 150, 210, and 270 days. The spray dried MP powders were sealed and stored at 25°C (for 0 (control), 60, and 120 days) and 40°C (for 0 (control), 30, 60, 90, 120, and 150 days). At each data point, the powders were analyzed for water activity (a [subscript]w), color, browning index (BI), FAST index (FI), hygroscopicity, caking, differential scanning calorimetry (DSC), and microstructure. In the DPW powders on storage, the main effect galactose was found to be significantly (p < 0.05) different for a [subscript]w, b*, BI, FI, and hygroscopicity and the interaction term lactic acid x galactose was found to be significantly (p < 0.05) different for L*, FI, and hygroscopicity. On storage, the time and the interaction effects time x galactose, time x lactic acid x galactose each were also found to have a significant (p < 0.05) effect on a [subscript]w, L*, and FI values. In MP powders, the main effect lactic acid was significant for a [subscript]w, a*, FI and hygroscopicity at 25℃ whereas at 40℃ the main effect lactic acid was significant for a [subscript]w, a*, b*, BI and FI. Overall, DPW and MP powders tended to absorb moisture on storage. However, the powders with higher amounts of lactic acid and galactose were more sensitive to absorbing moisture, giving rise to lumping and caking problems. These findings emphasize the importance of controlling the feed characteristics, production process, and storage conditions to reduce the Maillard reaction and limit caking in the final product and to enhance storage stability.
Keywords: Deproteinized whey powder; Milk permeate powder; Lactic acid; Galactose; Storage temperature/time